Iqbal and Nietzsche’s concept of eternal recurrence - Ahmad Dar, Bilal (Intellectual Discourse, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US KO AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Nietzsche has been a strong influence on some influential Muslim thinkers. He has been appropriated in divergent perspectives from mystical to nihilistic. Amongst the responses of Muslim thinkers to Nietzsche, Iqbal’s is perhaps the most articulate and interesting. The present paper has two main objectives: to examine a critical understanding of the Nietzsche’s most ambiguous idea of eternal recurrence and to explore Iqbal’s response to it. Nietzsche’s concept of eternal recurrence, seen by some philosophers as his most significant concept, has been questioned by Iqbal as the weakest link in his philosophy. Iqbal argues the case for transcendence and upholds the Islamic doctrine of fate which allows enough space for freedom of spirit in contrast to the absolutely deterministic view of Nietzsche. Iqbal’s sufi conception of the Perfect Man differs from Nietzsche’s Superman in the ability to deploy creativity and freedom for remoulding of the self and appropriating divine attributes. Thus, Iqbal deploys Islamic mystical resources in problematizing alternative models of human perfection and the response to tragic fact that a horizontal existence of man in an “indifferent universe” seems to be.